The Effect of the COVID-19 Pandemic on Government- and Market-Attitudes - Sandra Goff; John Ifcher; Homa Zarghamee; Alex Reents; Patrick Wade (Institute of Labor Economics (IZA), 2020)
We study the COVID-19 pandemic's effect on college students' government- and market-attitudes using within-subject comparisons of survey responses elicited before and after the onset of the pandemic. We find that support for markets significantly declines after the onset of the pandemic, with students less likely to think markets are efficient and more likely to think they can cause harm. Support significantly increases for bigger government though this does not translate to increased support for specific redistributive policies (i.e., the minimum wage, food stamps, and taxes on estates or extremely high income), nor to increased support for the government to play a role in the various specific capacities listed in the survey (e.g., ensuring access to healthcare, responding to natural disasters, and helping people get out of poverty). Both contentment with and trust in government significantly decrease after the onset of the pandemic. Subgroup analyses indicate these results are largely driven by more politically progressive students.
Keywords: H1; H5; P1; 330; COVID-19; pandemic; market attitudes; government attitudes; political ideology; redistribution